2001
DOI: 10.7124/bc.0005e0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics analysis of mutations and minihaplotypes of the phenylalanine hydroxylase gene in Ukraine

Abstract: Наведено результати молекулярно-генетичного аналізу мутацій та мінігаплотипів гена фенілаланінгідроксилази серед хворих на фенілкетонурію, членів їхніх родин та здорових індивідів (усього 445 осіб). Показано, що частота мажорної мутації R408W складає 57,3 %. Ідентифіковано вісім алельних варіантів STR-поліморфізму та 24 варіанти STR/VNTR мінігаплотипів. Показано достовірну нерівновагу у зчепленні між мутацією R408W та алелем 238 п. н. STR-поліморфізму.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Molecular genetic analysis of ÐÀÍ (phenylalanine hydroxylase) gene has established that R408W is a major mutation among PKU patients in Ukraine, and its frequency is 57 % [4]. The results of segregation analysis between this mutation and ÐÀÍ gene intragenic polymorphic minihaplotypes have shown two European centres of R408W origin (Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Molecular genetic analysis of ÐÀÍ (phenylalanine hydroxylase) gene has established that R408W is a major mutation among PKU patients in Ukraine, and its frequency is 57 % [4]. The results of segregation analysis between this mutation and ÐÀÍ gene intragenic polymorphic minihaplotypes have shown two European centres of R408W origin (Fig.…”
mentioning
confidence: 98%
“…Genotype analysis in patients with different clinical forms of PKU showed that «classic» severe form of the disease is characteristic of homozygotes and compound carriers of ÐÀÍ gene R408W mutation [4].…”
mentioning
confidence: 99%